2015
DOI: 10.3390/met5010383
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Rare Earth on the Microstructure and Impact Toughness of H13 Steel

Abstract: Studies of H13 steel suggest that under appropriate conditions, additions of rare-earth metals (REM) can significantly enhance mechanical properties, such as impact toughness. This improvement is apparently due to the formation of finer and more dispersive RE inclusions and grain refinement after REM additions. In this present work, the microstructure evolution and mechanical properties of H13 steel with rare earth additions (0, 0.015, 0.025 and 0.1 wt.%) were investigated. The grain size, inclusions and fract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
53
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 108 publications
(55 citation statements)
references
References 29 publications
2
53
0
Order By: Relevance
“…The size and morphology of non-metallic inclusions in steels have changed dramatically after adding Ce, La, Y and Ga [13][14][15][16][17]. Fu [18] and Gao [19] also reported that RE elements like Ce, La and Y can form highly stable oxides, oxy-sulphides and sulphides, which precipitate as solid particles in the melt due to their high melting temperatures. It was shown that the grain size of steel could be refined with a suitable amount of RE and resulted in enhanced impact toughness [16].…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations
“…The size and morphology of non-metallic inclusions in steels have changed dramatically after adding Ce, La, Y and Ga [13][14][15][16][17]. Fu [18] and Gao [19] also reported that RE elements like Ce, La and Y can form highly stable oxides, oxy-sulphides and sulphides, which precipitate as solid particles in the melt due to their high melting temperatures. It was shown that the grain size of steel could be refined with a suitable amount of RE and resulted in enhanced impact toughness [16].…”
Section: Introductionmentioning
confidence: 97%
“…The low mismatching, smaller surface energy, leads to a decrease of super-cooling required for nucleation, and results in refining of the grains. RE-inclusion possesses both high melting point and low mismatching between the matrix through the preliminary research work on the influence of RE on inclusions in 4Cr5MoSiV1 die steel by our group [19]. Moreover, the most common form of inclusions are found believed to be RE oxy-sulfides (Ce 2 O 2 S) with various RE contents (0, 0.015, 0.025 and 0.10 wt %) in 4Cr5MoSiV1 die steel [19].…”
Section: Carbides Evolution Induced By Re Additionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tomita [12] found that the addition of REE to vacuum-melted AF1410 steel can stabilize complex-inclusions and improve toughness. Gao et al substantially improved the toughness of H13 steel by adding 0.015 wt.% REE, which favors finer and more dispersive inclusions [13]. The addition of REE to welded metals to SAW DH32 steel facilitates both inclusions and a small lattice disregistry, which improves elongation, tensile strength, and impact toughness of welded metals [14,15].…”
Section: Introductionmentioning
confidence: 99%